Law in Commerce. - Sweeney, Brendan; Coleman, Andrew; Reily, Jennifer O (Australia : LexisNexis, 2016)
Law in Commerce 6th edition is an easily accessible text for business students. It includes coverage of the most important areas of business and commercial law including contracts, consumer law, trusts and company law.
Keywords: Commercial law; Contracts